Putative apoptosis effect of Momordica charantia Linn. extracts in human lung cancer cell line A549 - K Thiagarajan, Siroshini (2019)
Lung cancer is the leading cause of cancer related deaths worldwide comprising about 40% occurring in developing countries. Formerly traditional medicines were the major forms of cancer treatment prior to chemotherapeutic drugs. Momordica charantia or known as bitter melon is an edible fruit that has been used traditionally for cancer treatment. In this study, non-small cell lung cancer cells (NSCLC), A549 as an in vitro model to assess the apoptosis inducing effect of two variations Chinese (C) and Indian (I) bitter melon. The inhibitory effect of the hot aqueous (HA) and cold aqueous (CA) extracts was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The pro-apoptotic and derangement effect in A549 cells was observed under a fluorescence microscope using Hoechst 33358 (H33358) staining. The role of reactive oxygen species (ROS), caspase-3/7 and p53 was observed by examining the activity in the treated cells. Both hot and cold aqueous extraction of the bitter melons treated on NSCLC resulted a significant (p<0.05) decrease in cell viability and induced apoptotic cell death. H33358 staining showed that the crude extracts induced the typical nuclear apoptotic morphology and derangement of filamentous-actin. The apoptosis of NSCLC cells was accompanied by the increase in ROS, caspase-3/7 and p53 expression. Further study using flowcytometry also confirmed the apoptosis activity suggesting the results obtain were aligned with the intrinsic mitochondria apoptosis pathway. Generally all crude water-soluble extracts exhibited apoptosis via the same pathway. Among the crudes extracts, Chinese bitter melon hot aqueous extract (CHA) showed a significant (p<0.05) anti-cancer activity to cisplatin acting as a positive control. CHA also increased the Caspase 3/7 activity by 1.6 folds while 5 folds in ROS activity. With CHA significantly (p<0.05) increasing the apoptotic activity when compared to CCA, IHA, and ICA, CHA may induce the intrinsic apoptotic pathway due to their rich bioactive chemical constituents as shown in the Liquid Chormatography-Mass Spectrometry (LC-MS) result. These findings propose that the anti-proliferative effect of CHA at inhibitory concentration, IC50 of 32.5±0.18μg/ml was associated with apoptosis by regulating mitochondria destruction by increasing caspase-3/7 activity. CHA also induces p53-dependent apoptosis of A549 in a ROS-dependent manner subjecting to 34.5% apoptotic cells.